The Influence of Family Gratitude and Social Support on Psychological Well-being of Batak Toba Parents Who Do Not Have Son - Nenny Ika Putri Simarmata; Nancy Naomy G.P Aritonang; Katrina Dewita Lumbantoruan; Desi Natalia Hutagalung (Universitas Ahmad Dahlan, 2024)
The Batak Toba family adheres to a patrilineal family system, where couples are expected to have sons to continue the clan. Batak parents who do not have sons often feel stressed, anxious and depressed. This research aims to examine the influence of gratitude and social support on the psychological well-being of Batak Toba parents who do not have sons. A total of 50 Batak Toba fathers and mothers who did not have sons were the research sample. Data collection was carried out through online and offline questionnaires. This research uses quantitative methods with a correlation design, and data analysis uses multiple linear analysis with SPSS 22. The findings of this research show that gratitude has a positive effect on the psychological well-being of Batak Toba parents who do not have sons, this result strengthens existing literature. These results can also encourage policies to create mental health services and social programs that support them and reduce the stigma against Batak parents who do not have sons.